WACANA, KUASA DAN AGAMA DALAM KONTESTASI PILGUB JAKARTA TINJAUAN RELASI KUASA DAN PENGETAHUAN FOUCOLT (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
Religion Blasphemy addressed to Jakarta Governor who is also a candidate for Jakarta Governor Election 2017 is the beginning of a series of polemic along process of Jakarta Governor Election 2017. This case triggers friction between Islamic society as a civil society and government as authority. This research explored this case by using theory of power relations Foucault. The result shows that the mass movement of Islamic society is power from Islamic society knowledge. Power structure tries to discipline this movement by hegemony in form of discourse. However, hegemonic discourse from civil society (Islamic society) also tries to challenge. The fight of hegemonic in form of discourse becomes so viral in all media, element and institution. This research shows that the discourse of Leader and Diversity is a signifier empty which be contestation of giving meaning